Teaching in a municipal network: far away from rural education and popular education / Ensino em rede municipal: bem distante da Educação do Campo e da Educação Popular - Maria Aparecida Vieira de Melo (Universidade Estadual de Alagoas, 2019)
Analyze the situation of public schools in the light of the ideas of Rural Education and Popular Education was the purpose of the research that gave rise to this article, developed in the city of Canhotinho, located in the Agreste Pernambucano. She was guided by the questions: how are developed pedagogical practices in municipal schools Canhotinho - PE situated in rural contexts? That approaches such practices process with the ideals of ural Education and Popular Education? Their goal was to analyze psicopedagogas practices in municipal schools in rural contexts. Canhotinho in the wild of Pernambuco, was the locus of research. Interviews It is effected with 7 teachers that Municipal Network and processed 10 observation sessions in the classroom. It could be observed that still lingers, alarmingly, the practice of multigrade classes, which affects many psychopedagogical developments. It is also noticed the prevalence of notably urbanocêntricas characteristics that separate these realities of rural education of ideology and also of popular education. In addition, research has given rise to considerations that seem relevant on the issue of the identity of the teacher (a) Field and teacher (a) in the field.